Pengaruh Media Sosial Terhadap Penyimpangan Perilaku Pada Siswa - Rosyidah Rosyidah (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2015)
Today the use of facebook / twitter has become a daily routine. The number of students using the facebook/twitter, making them aside obligations, even making it a hobby without knowing the time. Seeing the development of facebook / twitter that many favored particularly adolescents, as well as the resulting negative impact, encourage researchers to conduct research on the impact of media facebook / twitte against deviant behavior in students. The purpose of this study was to determine the effect of media facebook/twitter to deviations of student behavior MTs Muhammadiyah 1 Mungkid. This research is a quantitative research with the entire student population of MTs Muhammadiyah Mungkid. The sample used a number of 62 students with proportional random sampling. Data collection method used is the questionnaire method and documentation. Data analysis technique using linear regression statistical test. The results showed that there was a significant relationship between media use facebook/ twitter to deviations of student behavior MTs Muhammadiyah 1 Mungkid. It is based on linear regression analysis obtained regression coefficient of 1.098 with significant value 0.000> 0.05. So when the media use facebook / twitter increases, the deviant behavior of students will also be increased.